Problematics and genre originality of Y. Polyakov’s novel “Gypsum Trumpeter” - Narmina E. Ibadova; Michail M. Golubkov (RUDN Journal of Studies in Literature and Journalism, 2020)
The article is devoted to the analysis of problems and genre originality of Y. Polyakov's three-part novel “Gypsum trumpeter”. The novel, written in the style of grotesque realism, is multifaceted, it contains many insert stories of historical, detective, and lyrical nature. Such a genre form serves the writer's intention to expose the vicious phenomena of the surrounding reality. The same goal is served by a wide arsenal of skillfully used poetic devices: occasional words and phrases, author's neologisms, detailed hyperbolas and litotes, unexpected comparisons. The novel abounds in aphorisms. The precedent-setting phenomenon is used in the titles of most chapters of the work. The author's attitude to the characters is shown in the “talking” surnames, bright portrait sketches. Subject-household details, epigrams give vivacity to the narrative. The novel is devoted to creative people, and in the text a lot of space is occupied by reflections and disputes about the purpose of art, about what real art should be. Paying tribute to the servants of the Muse, the author tells about inspiration, hard creative work and the torments of creation.